2015
DOI: 10.1016/j.sna.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Extended PDMS stiffness range for flexible systems

Abstract: a b s t r a c tThe use of polymers in the context of flexible systems such as flexible sensors leads to an incompatibility issue: on the one hand, the flexibility of the polymer must not be to the detriment of the fabrication process, e.g. excessive thermal expansion leading to process failure and on the other hand, certain applications will require high flexibility and also a specific mechanical stiffness, e.g. artificial skin, smart clothes, flexible screen. In other words, a compromise is necessary between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
97
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 47 publications
9
97
0
Order By: Relevance
“…NH behavior and when analyzed against the Ogden model, it is possible to capture an exponent of N = 2.40 ± 0.14, again nearly identical to the NH response. 4 Figure 3: Variation of the average shear modulus measured for PDMS samples as a function of the cross-linking density, in comparison with our previous measurements [46], as well as the measurements of Wang et al [92] and Seghir and Arscott [93].…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…NH behavior and when analyzed against the Ogden model, it is possible to capture an exponent of N = 2.40 ± 0.14, again nearly identical to the NH response. 4 Figure 3: Variation of the average shear modulus measured for PDMS samples as a function of the cross-linking density, in comparison with our previous measurements [46], as well as the measurements of Wang et al [92] and Seghir and Arscott [93].…”
Section: Resultsmentioning
confidence: 66%
“…Unfortunately, there are no reports of measurements of such second constants reported in literature for comparable samples. Seghir and Arscott [93] use a generalized MR to analyze their results, but only report the shear modulus as presented in Fig.3. Kim et al [94] report softer responses for PDMS films of 15:1 (less than half the shear modulus measured here) and thus a fair comparison is not possible.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, different PDMS mixing ratios and baking processes are required to mix with the SU‐8—for an easier understanding of the preparation of the PDMS, the authors direct readers to refer to our previous work in which the tunability of PDMS stiffness is demonstrated and analyzed depending on the base/curing agent mixing ratio, baking time, and temperature. PDMS mixtures were first prepared by mixing the base and the curing agent with different weight ratios (10:1, 4:1, and 2:1).…”
Section: Preparation Of Pdms/su‐8 Samplesmentioning
confidence: 99%
“…Study and characterization of PDMS's mechanical, chemical and optical properties are reported for specific cases in the literature; some fabrication methods are also mentioned to modify properties such as (a) curing and baking conditions, (b) different proportions of curing base agent, (c) different types of PDMS and other polymers, (d) inclusion of other molecules or particles and (e) elaboration of samples with different forms and sizes [13,[28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties measurements of PDMS's samples are also detailed for predetermined synthesis parameters; relevant examples are the components´ratio of base mixture: catalyst (ratios varying from 2:1 to 33:1) [9,16,21,28], the curing temperature applied (from room temperature up to 310°C) [30,35], or the curing time (18 min to 48 h) [32,41]. Reports indicate that Young's modulus, compressive and shear moduli vary in the ranges of 12 kPa-3 GPa, 117.8 MPa-186.9 MPa and 100 kPa-3 MPa, respectively [14,18,22,35,37,42,43].…”
Section: Introductionmentioning
confidence: 99%